Minimal Compared With Standard Monitoring During Sofosbuvir-Based Hepatitis C Treatment: A Randomized Controlled Trial. (19th January 2020) - Davis, J S; Young, M; Marshall, C; Tate-Baker, J; Madison, M; Sharma, S; Silva, C; Jones, T; Davies, J
Abstract: Background: Oral direct-acting antiviral agents (DAAs) for hepatitis C virus (HCV) became government subsidized in Australia in March 2016, bringing the interferon era to a close. The ideal monitoring schedule for patients receiving DAAs is unclear. Methods: This study is a randomized controlled trial comparing standard with minimal monitoring in adults receiving sofosbuvir-based therapy for HCV genotypes 1 or 3. Exclusion criteria were cirrhosis or predicted poor adherence. Standard monitoring included blood tests and face-to-face clinic visits at treatment weeks 4 and 12 and 12 weeks after treatment completion. Minimal monitoring included a phone call at weeks 4 and 12 and one set of blood tests plus a clinic visit 12 weeks after treatment completion. The coprimary outcomes were as follows: (1) proportion of participants with sustained virological response; (2) staff time spent on patient support; and (3) patient satisfaction on a 10-point Likert scale. Results: Thirty-six patients were randomized to standard monitoring and 38 to minimal monitoring. Sustained virological response at 12 weeks after the end of treatment was documented in 32 of 36 (89%) in the standard versus 37 of 38 (97%) in the minimal monitoring group. Staff time was nonsignificantly longer in the standard group (median 69 [interquartile range IQR, 54–80] versus 52 [IQR, 40–75] minutes). Patient satisfaction scores were not different (mean 9.8 of 10 standard versus 9.6 of 10 minimal group). There was no difference in adverse events or unplanned hospital visits; mean per-patient blood test costs were higher in the standard monitoring group (432 versus 123, P < .001). Conclusions: On-treatment monitoring with blood tests and clinic visits may not be necessary during sofosbuvir-based HCV treatment in selected patients. Abstract : In this pilot, randomized, controlled trial including 74 patients treated for HCV with sofosbuvir-based regimens, a strategy of minimal monitoring led to an equal cure rate with less costs compared with standard monitoring.